PENGEMBANGAN BAHAN AJAR SAINS MINI BOOK PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS IV SD SWASTA PELANGI MEDAN - Hutapea, Riana Rosinta Marito; Simanihuruk, Lidia; Manurung, Imelda Free Unita; Aulia, Sri Mustika; Ratno, Suyit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science and Social Studies (IPAS) learning on the topic of changes in the states of matter in elementary schools requires teaching materials that can help students understand concepts clearly and in an engaging way. However, based on the results of observations at SD Swasta Pelangi Medan, the teaching materials used are still limited to textbooks and Student Worksheets (LKPD), so the presentation of the material is less interesting and is not supported by varied learning media. In addition, limited facilities such as the unavailability of projectors cause the use of technology-based teaching materials to not be implemented optimally. This study aims to determine the validity, practicality, and effectiveness of Canva-based Science Mini Book teaching materials on the topic of changes in the states of matter in grade IV of SD Swasta Pelangi Medan. This research is a Research and Development (R&D) study using the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 20 fourth-grade students of SD Swasta Pelangi Medan. The data collection techniques used were observation, interviews, questionnaires, tests, and documentation. The results showed that the Science Mini Book teaching material obtained a validation percentage of 86% from media experts, 90% from material experts, 96% from education practitioners, and a student response percentage of 97.4%, with an overall average of 92.35% which is categorized as very feasible. Therefore, the Canva-based Science Mini Book teaching material is declared valid, practical, and effective so that it is feasible to be used in IPAS learning on the topic of changes in the states of matter in grade IV of elementary school.